Epistolary Autobiographies during Pre-Independence Period: Exploring the Epistolary Autobiographies of Raja Ram Mohan Roy and Kasi Prasad Ghose (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present article deals with the epistolary form adopted by two writers, namely Raja Ram Mohan Roy and Kasi Prasad Ghose during Independence for their short autobiographies. The two writers have chosen this literary genre to articulate their personal feelings and ideas for which every reader would respond with a sense of intimacy. These writers, as they belong to the early period of Indo-Anglian prose writing, would enable the reader to peep into the exciting period of Indian Renaissance.